The impact of hormonal contraceptives on breast cancer patients hospital Dr. Sardjito - Nuratul Awaliyah; Heru Pradjatmo; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
The use of hormonal contraceptives relates with the incidence of breast cancer in Dr. Sardjito Yogyakarta Purpose: This study aimed to determine whether women using the contraceptive pill can cause breast cancer.Methods: A case control study was conducted August to October 2016 with 250 patients.Results: Factors that were associated with breast cancer were: type of pill with adjusted OR = 1.66 (95% CI = 1.21 to 2.28; p = 0.001), duration of consumption with adjusted OR = 2.25 (95% CI = 1.04 to 4.84; p = 0.037), and the period of last hormonal contraception with adjusted OR = 2.41 (95% CI = 1. 15 to 5.05; p = 0.020). This study showed that the use of hormonal contraceptives raises the risk of breast cancer.Conclusion: Women should play an active role in breast cancer prevention programs through early detection and treatment. Health services need to explain the potential risks of hormonal contraceptive.